2019
DOI: 10.1111/sji.12819
|View full text |Cite
|
Sign up to set email alerts
|

Association of CTLA‐4, TNF alpha and IL 10 polymorphisms with susceptibility to hepatocellular carcinoma

Abstract: Our aim was to evaluate the association of genetic polymorphisms of immunoregulatory molecules with susceptibility to hepatocellular carcinoma (HCC). The polymorphisms in CTLA‐4 (−318 T/C, CT60 G/A), TNF (−238 G/A, −308 G/A) and IL10 (−592 C/A, −819 C/T) were genotyped by PCR and DNA sequencing. The functional relevance of the polymorphisms was examined by ELISAs, in vitro lymphocyte proliferation assay and cytotoxic assay. The CTLA‐4 −318 TC/TT, CTLA‐4 CT60 GG, IL10 −592 CA and −819 CT/TT variants, CTLA‐4 −31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…These results are in agreement with those of a previous study (Wang et al, 2019) who found that CT was the most common genotype in HCC group (P value < 0.05). Few studies (Aroucha et al, 2016;Wang et al, 2019) found that T allele was the most common allele in HCC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with those of a previous study (Wang et al, 2019) who found that CT was the most common genotype in HCC group (P value < 0.05). Few studies (Aroucha et al, 2016;Wang et al, 2019) found that T allele was the most common allele in HCC.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those of a previous study (Wang et al, 2019) who found that CT was the most common genotype in HCC group (P value < 0.05). Few studies (Aroucha et al, 2016;Wang et al, 2019) found that T allele was the most common allele in HCC. Moreover, reports (Li et al, 2018;Maurya et demonstrated that TT genotype of IL-10(−819) gene was found in 20 patients (50%) with HCV infection and 25 patients (62.5%) with HCC.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, some studies have focused on the relationship between CTLA4 SNPs and susceptibility to HCC, and Wang's research demonstrated that CTLA4 could affect susceptibility to HCC via changing the immune status of the individuals. 34 TISIDB results indicated that MFAP2 expression is closely related to Tregs and some immunological checkpoints which have recently received more and more attention, such as CTLA4, TIGIT in HCC. Therefore, inhibitors that target these immune checkpoints might be particularly effective in the treatment of HCC patients, especially when used in combination with MFAP2 inhibitors.…”
Section: Discussionmentioning
confidence: 98%
“…Concerning the -1082 A/G IL-10 SNP, there was a lack of association between this genetic polymorphism and VFL. These three IL-10 SNPs are located in the promoter region of the gene ( 27 ). The T allele of the -819 T/C SNP, the A allele of the -592 A/C IL-10 SNP, and the A allele of the -1082 A/G IL-10 SNP were associated with lower IL-10 concentration, while the CCG haplotypes of these SNPs, respectively, were related to higher IL-10 secretion ( 28 ).…”
Section: Discussionmentioning
confidence: 99%